The Home and the World - Tagore, Rabindranath, 1861-1941; Tagore, Surendranath, 1872-1940 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Home and the World" by Rabindranath Tagore is a novel published in 1916. Set against India's independence movement, it explores the clash between Western ideals and traditional values through a fraught love triangle. Bimala, a devoted wife, finds herself torn between her rational, peace-loving husband Nikhilesh and his charismatic guest Sandip, a revolutionary who stops at nothing to achieve his nationalist goals. As political upheaval sweeps through Bengal, Bimala's awakening forces her to navigate between domestic duty and the intoxicating pull of radical change. (This is an automatically generated summary.)
Wikipedia page on this work: https://en.wikipedia.org/wiki/The_Home_and_the_World
Release date is 2004-12-01
Original html version created at eldritchpress.org by Eric Eldred. This eBook was produced by Chetan Jain, Viswas G and Anand Rao at Bharat Literature
Keywords: India -- History -- Autonomy and independence movements -- Fiction